KESADARAN POLITIK BERKETUHANAN SEBAGAI DASAR UNTUK MEWUJUDKAN KESEJAHTERAAN RAKYAT INDONESIA - Putra, Andri Azis; Kuswanjono, Arqom; Munir, Misnar (JURNAL AL-AQIDAH, 2020)
Welfare is one of the significant problems in human life. All aspects of human life politically will always be related, both as elements and indicators of welfare conditions. Consequently, the state is an organization and authority that can provide a measure and effectively regulate all efforts in the realization of people's welfare. However, practically "people's welfare" in Indonesia is still in a quarrel state with the targets-setting. This research is library research with a hermeneutic-philosophical approach. Political Theology, as a branch of the Philosophy of Religion, will be used as the primary approach by involving methodical elements that are balanced and consistent with research. Additionally, the involvement of other scientific disciplines such as political philosophy, social philosophy, and economics will enrich this research. This research shows that the efforts carried out to realize the welfare of the people is dominantly incompatible with the needs of the subjects receiving welfare facilities. The source of this problem is relying on the perspective of governmental values. New awareness and responsibility are needed to build a structure with a divine and human nature. This awareness arises as an implementation form of worship to God and also responsibility for that worship to fellow human beings.